Violence and discrimination against street vendors in the pandemic scenario - Hernandez Linares, Daniel Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This research analyses how the pandemic has affected informal vendors and their families. Taking into account that the informal economy has been affected due to the measures taken by the government, which were linked to limiting the use of public space by people, we seek to analyze the following aspects: how has how they sell and promote their products changed during the pandemic, how have they managed their economy, what benefits have they received from the government and what is their opinion of the economic reactivation proposed by the government?